ONE YEAR PILOT IMPLEMENTATION OF THE NEW GREEK GEOGRAPHY CURRICULUM IN PRIMARY EDUCATION - Aikaterini I. KLONARI; Achilleas MANDRIKAS; Anastasia MELISTA; Maria TZOURA (European Journal of Geography)
The aim of this paper is to present the results of the Greek primary education Geography Curriculum piloted during the school year 2011-2012. The sample consisted of 43 primary school teachers, from different Greek regions, who piloted the new Geography Curriculum and from whom semi-structured interviews were obtained. Furthermore, 36 lesson plans and worksheets produced by teachers during piloting were analyzed. The results from the interviews showed that teachers were generally satisfied with the new Geography Curriculum, seemingly having captured to a large extent the aims and the objectives; they ascertained absolute correspondence between intended learning outcomes and proposed activities, considered the teacher’s guidebook to be highly satisfactory and valued the teacher training accompanying the pilot scheme as being very effective. Moreover, an analysis of lesson plans and worksheets showed that teachers created activities and adopted teaching methods that included the essential characteristics of the Geography Curriculum, both in terms of development of the basic concepts and the use of new technologies.